2017
DOI: 10.1021/acssuschemeng.6b02761
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Ni Nanoparticles Supported on Hierarchical Porous Nitrogen-Doped Carbon for Hydrogenolysis of Kraft Lignin in Flow and Batch Systems

Abstract: Ni nanoparticles supported on nitrogen-doped carbon (NDC) prepared via salt-melt synthesis with a hierarchical porosity were successfully applied as the catalyst for the degradation of Kraft lignin. It is shown that Ni-NDC is more efficient when compared to Ni nanoparticles deposited on an N-free carbon support, prepared with similar porosity features (Ni–C) and to Ni nanoparticles deposited on a commercial carbon (Ni-Cref). The efficiency of these materials was compared for reactions performed both in batch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…The porous carbon supports were prepared by salt‐melt templating followed by carbonisation as described previously . An eutectic salt mixture of KCl and ZnCl 2 (450 mg, 1:2 mass ratio) was mixed in a mortar with glucose (150 g) as the carbon precursor for the synthesis of the nitrogen‐free C Glucose support.…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…The porous carbon supports were prepared by salt‐melt templating followed by carbonisation as described previously . An eutectic salt mixture of KCl and ZnCl 2 (450 mg, 1:2 mass ratio) was mixed in a mortar with glucose (150 g) as the carbon precursor for the synthesis of the nitrogen‐free C Glucose support.…”
Section: Methodsmentioning
confidence: 79%
“…Owing to the high electric conductivity of such metal‐free catalysts, metal‐free catalysis is particularly important in the field of electrocatalysis . On the other hand, nanocarbon can act as a stabilizing agent or support for catalytically active sites (in most cases metallic or other inorganic nanoparticles) . Nanocarbon materials are attractive catalyst supports because of their high chemical and thermal stability as well as their weak chemical interaction with the metal particles facilitating the formation of active species .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon support can also be modified to increase the catalytic activity of hydrogenolysis [98,99]. Doping the carbon support with electron donor atoms such as nitrogen should lead to (1) reduced work function of the support; (2) enhanced partial electron transfer between Ni and the support; (3) increased chemically active sites; (4) increased Ni particle dispersion.…”
Section: Monometallic Ni-based Catalysts For Hydrogenolysis Of Ligninmentioning
confidence: 99%
“…Doping the carbon support with electron donor atoms such as nitrogen should lead to (1) reduced work function of the support; (2) enhanced partial electron transfer between Ni and the support; (3) increased chemically active sites; (4) increased Ni particle dispersion. Thus, it has been shown that Ni-NDC (nitrogen doped carbon) enhanced the catalytic hydrogenolysis of lignin compared with undoped carbon supports [98]. Using NiMgAl layered double hydroxides and lignosulfonate to prepare the Ni metal catalyst supported on MgAl modified carbon support, the 3d electron distribution of surface layer Ni can be altered to promote highly selective C-O bond cleavage [99], while the Ni/C catalysts only showed high conversion but lower monomer selectivity and the mixed oxide Ni/MgAlO showed little or no activity.…”
Section: Monometallic Ni-based Catalysts For Hydrogenolysis Of Ligninmentioning
confidence: 99%